2021
DOI: 10.1093/ecco-jcc/jjab007
|View full text |Cite
|
Sign up to set email alerts
|

Course of Disease in Patients with Microscopic Colitis: A European Prospective Incident Cohort Study

Abstract: Background and Aims The disease course of microscopic colitis [MC] is considered chronic but benign. However, this assumption is based on mainly retrospective studies, reporting on incomplete follow-up of selective cohorts. Systematic, prospective and unbiased data to inform patients and healthcare professionals on the expected course of the disease and real-life response to therapy are warranted. Methods A prospective, pan-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 44 publications
5
12
0
Order By: Relevance
“…A recent European prospective cohort study showed approximately half of MC patients have a relapsing disease course, particularly during the first year of diagnosis. 34 There were a few limitations to this study including the predominantly white population in Olmsted County, MN. In addition, despite county residents being socioeconomically similar to the US population, residents have a higher level of education and a higher percentage of people working in the health care industry compared with residents nationwide.…”
Section: Discussionmentioning
confidence: 96%
“…A recent European prospective cohort study showed approximately half of MC patients have a relapsing disease course, particularly during the first year of diagnosis. 34 There were a few limitations to this study including the predominantly white population in Olmsted County, MN. In addition, despite county residents being socioeconomically similar to the US population, residents have a higher level of education and a higher percentage of people working in the health care industry compared with residents nationwide.…”
Section: Discussionmentioning
confidence: 96%
“…MC is an uncommon condition, and biologic therapy remains infrequently utilized in MC. For example, in a recent prospective incident cohort study that included 381 patients, none of the patients required biologic therapy within the first year of MC diagnosis [31]. Consequently, most of the included studies in our meta-analysis were small sized.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the clinical course over time in a cohort of 318 patients with microscopic colitis and a mean age of 64 years with complete 1-year follow-up revealed that 49% had a chronic active or relapsing disease course; 40% achieved sustained remission after treatment, and 11% had a quiescent course ( Verhaegh et al, 2021 ). In general, symptoms and quality of life improved after 3 months of follow-up.…”
Section: Prognosismentioning
confidence: 99%
“…In general, symptoms and quality of life improved after 3 months of follow-up. A relapsing or chronic active disease course was associated with considerably more symptoms and an impaired quality of life after 1 year ( Verhaegh et al, 2021 ). Previously, another study evaluating the natural history of microscopic colitis with a median follow-up of 8 years revealed that 75% of patients achieved prolonged remission without therapy for more than a year ( Fernández-Bañares et al, 2016 ).…”
Section: Prognosismentioning
confidence: 99%